Upconversion Nanoparticles: Synthesis, Surface Modification, and Biological Applications - Wang, Meng (2011)
New generation fluorophores, also termed upconversion nanoparticles (UCNPs), have the ability to convert near infrared radiations with lower energy into visible radiations with higher energy via a non-linear optical process. Recently, these UCNPs have evolved as alternative fluorescent labels to traditional fluorophores, showing great potential for imaging and biodetection assays in both in vitro and in vivo applications. UCNPs exhibit unique luminescent properties, including high penetration depth into tissues, low background signals, large Stokes shifts, sharp emission bands, and high resistance to photo-bleaching, making UCNPs an attractive alternative source for overcoming current limitations in traditional fluorescent probes. In this review, we discuss the recent progress in the synthesis and surface modification of rare earth doped UCNPs with a specific focus on their biological applications.